Prognostic markers of recurrence and survival in rectal cancer treated with neoadjuvant chemoradiotherapy and surgery. (2nd May 2018) - Abdalmassih, Michael; Sivananthan, Gokulan; Raizman, Zachary; Lambert, Pascal; Wirtzfeld, Debrah; Bashir, Bashir; Wightman, Robert; Daniel, Kroeker; Nashed, Maged
Aim: To identify markers of recurrence and survival in patients with locally advanced rectal cancer who received neoadjuvant chemoradiotherapy and surgery.Materials & methods: A total of 280 patients were identified in Manitoba between 2007 and 2012. Demographics and clinical data were collected. Cox regression models were used to identify outcome predictors.Results: A total of 53 patients achieved pathological complete response (pCR) and 160 patients received adjuvant chemotherapy (ACT). The median follow-up duration was 2.06 years. Recurrence and survival rates at 5 years were 33.2 and 77.0%, respectively. pCR and lymphovascular invasion predicted recurrence. pCR and ACT predicted better survival.Conclusion: pCR is a significant predictor of recurrence and survival and may be considered as an oncological end point. The patients who achieve pCR may not derive additional survival benefit from ACT.